Credit constraints and agricultural technology adoption: Evidence from Nigeria - Balana, Bedru; Oyeyemi, Motunrayo (International Food Policy Research Institute, 2020)
The agricultural sector in Nigeria is characterized by low productivity that is driven by low use of modern agricultural technologies, such as improved seed, chemical fertilizer, agrochemicals, and agricultural machinery. Poor access to credit is claimed to be one of the key barriers to adoption of these technologies. This study examines the nature of credit constraints among smallholder farmers – whether smallholders are credit constrained or not and the extent to which credit constraints emanate from supply-side or demand-side factors. Using multinomial probit and seeming unrelated simultaneous equations econometric models with data from the 2018/19 Living Standards Measurement Study-Integrated Surveys on Agriculture (LSMS-ISA) for Nigeria, the study investigates the factors affecting credit access and the effects of these credit constraints on adoption of four agricultural technologies – inorganic fertilizer, improved seed, agrochemicals, and mechanization. The results show that about 27 percent of survey households were found to be credit constrained – 12.8 percent due to supply-side factors and 14.2 percent due to demand-side factors. Lack of access to information and communication technology, extension services, and insurance coverage are the major demand-side factors negatively affecting smallholder’s access to credit. Registered land tiles and livestock ownership enhance credit access. Credit constraints manifests themselves differentially on the adoption of different agricultural technologies. While adoption of inorganic fertilizer and improved seed are significantly affected by credit constraints from both the supply and the demand-sides; use of agricultural machinery is affected only by demand-side factors, while use of agrochemicals is not affected from either supply or demand-side credit factors. From a policy perspective, our findings indicate that improving credit access via supply-side interventions alone may not necessarily boost use of modern agricultural technologies by smallholder farmers in Nigeria. Demand-side factors, such as access to information, extension services, and insurance cover, should equally be addressed to mitigate the credit constraints faced by smallholders and increase their adoption of modern agricultural technologies and improve their productivity.